Antibiotic Concentrations Affect the Virulence of Klebsiella quasipneumoniae subsp. similipneumoniae Isolates - Berfin Eroğlu; Eda Delik; Burcu Emine Tefon-Öztürk (Cellular Microbiology)
Klebsiella species are becoming a major global public health concern. In particular, the increase in multidrug-resistant strains is a cause for concern. This study was aimed at determining the antibiotic susceptibility of two different isolates of Klebsiella quasipneumoniae subsp. similipneumoniae and determining the virulence characteristics and bacterial morphology under subminimum inhibitory concentrations (sub-MICs) of antibiotics. In this study, two multidrug-resistant K. quasipneumoniae subsp. similipneumoniae isolates were identified, one of which was clinical, and the other was isolated from freshwater. The MICs of the antibiotics meropenem, chloramphenicol, ciprofloxacin, and kanamycin were determined for these isolates. The effects of the sub-MICs on the virulence and morphological characteristics of the bacteria were investigated in comparison with K. pneumoniae (ATCC 13883). The MICs of meropenem, chloramphenicol, ciprofloxacin, and kanamycin were 0.04, 20, 2, and 8 μg/mL in the clinical isolate; 0.2, 15, 5, and 2 μg/mL in the freshwater isolate; and 0.03, 3, 0.1, and 0.3 μg/mL for K. pneumoniae. The biofilm-forming ability of K. quasipneumoniae subsp. similipneumoniae isolates decreased with antibiotic sub-MICs. Siderophore activity increased only with MIC/4 of kanamycin and MIC/2 of chloramphenicol in the clinical isolate (p>0.05). Furthermore, bacterial morphology and expression of virulence genes were affected differently by the sub-MICs. This study showed that biofilm formation decreased and that the changes in bacterial morphology and expression of virulence genes were very different in the presence of 1/2 and 1/4 sub-MIC antibiotics.